- #1

- 40

- 0

\(\displaystyle y''(x)+y'(x)+F(x)=0\)

Pleas me a idea

Pleas me a idea

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- #1

- 40

- 0

\(\displaystyle y''(x)+y'(x)+F(x)=0\)

Pleas me a idea

Pleas me a idea

- #2

- 1,952

- 983

Let y'(x) = v(x). Then your equation becomes v'(x) + v(x) = -F(x)\(\displaystyle y''(x)+y'(x)+F(x)=0\)

Pleas me a idea

Now you have a first degree linear ordinary differential equation. You can't write down a final answer, but there is a method by which you can write it out in terms of F(x)...

-Dan

- #3

Science Advisor

Homework Helper

- 43,008

- 974

(You could also see that by writing the equation as $v'= \frac{dv}{dt}=-v$ so that $\frac{dv}{v}= -dt$ and integrating: $ln(v)= -t+ C'$ so $v= e^{-t+ C'}= Ce^{-t}$ with $C= e^{C'}$.)

To find a solution to the entire equation, look for a solution of the form $v(t)= u(t)e^{-t}$ where u is a function to be found. $v'= u'e^{-t}- ue^{-t}$ so $v'+ v= u'e^{-t}- ue^{-t}+ ue^{-t}= u'e^{-t}= -F$. Then $u'= =Fe^{t}$ and $u= -\int Fe^{t}dt$.

The general solution to the entire equation is the general solution to the associated homogeneous equation plus that solution to the entire equation:

$v= y'= Ce^{-t}- \left(\int_0^t F(s)e^sds\right)e^{-t}$

Now y is the integral of that.

Share:

- Replies
- 1

- Views
- 968

- Replies
- 7

- Views
- 1K

- Replies
- 28

- Views
- 1K

- Replies
- 3

- Views
- 123

- Replies
- 2

- Views
- 896

- Replies
- 4

- Views
- 1K

- Replies
- 12

- Views
- 2K

- Replies
- 2

- Views
- 889

- Replies
- 7

- Views
- 1K

- Replies
- 4

- Views
- 2K